STACK VENTILATION SOLUTIONS FOR HOMES IN THE TROPICAL CITY OF JAKARTA: CASE STUDY OF A HOUSE AT NORTH JAKARTA - Chandra, Budijanto; Budi Listijono, John; Oenang, Arnold (Universitas Ciputra Surabaya, 2026)
The growing problem of urbanization has led to the expansion of densely populated cities such as Jakarta, resulting in issues including limited green spaces, elevated vehicle pollution, and industrial pollution. Tropical climates with high temperatures and humidity require indoor thermal comfort maintenance, especially due to climate change. An approach to achieving thermal comfort in tropical regions is the use of natural ventilation, such as stack ventilation. This stack ventilation will increase airflow, improve thermal comfort, and reduce electricity use by reducing reliance on air conditioning. Stack ventilation does not require a prevailing wind around the dwelling, as it relies on the upward air movement driven by buoyancy forces. Stack ventilation, being independent of outdoor wind speeds, can also mitigate the pollutants carried by outdoor wind currents, thereby improving indoor air quality and creating a healthier living environment. This study used an exploratory empirical case study approach to study a residence that has effectively utilized stack ventilation and achieved awards for its energy conservation initiatives. Stack ventilation can be effectively utilized in dwellings with a void and in near-isothermal tropical conditions by integrating an induced-solar-heat glass chamber at the apex of the solar chimney. This configuration creates a heated zone that facilitates the ascent of less dense air, which is then expelled from the top of the shaft. This study's findings are a preliminary insight for the implementation of stack ventilation in residential properties. Stack ventilation is suggested for residential homes in densely populated cities like Jakarta, effectively utilizing voids to facilitate the system with an induced solar-heat chimney.